Methodological approaches for regime performance towards achieving socio-economic democratic consolidation in developing societies - Ku Samsu, Ku Hasnita; Abbas, Ali Ibrahim (Globeedu Group, 2017)
This paper describes a research methodology approach for regime performance towards achieving socio-economic democratic consolidation in developing societies. The emphasis of this paper is on regime performance of Governor Gaidam towards achieving socio-economic democratic consolidation in Yobe state, 2009-2015. As part of a wider study, this paper provides the study area, research design, data collection and analysis procedure adopted for the study. Importantly, the approaches adopted and discussed in this paper become the research foundation of the first author for his PhD study. To achieve the overall aim of the paper, we specifically discussed the profile of Yobe state emphasizing creation, population, culture, geography, landmass, political economy, governance and administrative structure. Beyond the socio-economic profile of Yobe state described as one of the most underdeveloped states in Nigeria, the paper discussed the qualitative designs and approaches adopted in the PhD study. Therefore, issues of selection of informants, sources of data, methods of data collection, data analysis procedures and techniques were explained. Finally, issues of validity and reliability and social science ethical considerations which generally guided the overall study from start to finish are explained.